2015
DOI: 10.1167/tvst.4.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Experimental Drug Eluting Suprachoroidal Microstent as Glaucoma Drainage Device

Abstract: The presented data serve as a proof of principle study for the concept of a suprachoroidal drug eluting microstent. Future device improvements will be focused on the design of LDD systems and the use of specific anti-inflammatory or antifibrotic agents with less cytotoxicity compared to MitC or PTX. Long-term animal studies using a reliable glaucoma model will be a further step towards clinical application and improvement of surgical glaucoma therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
0
19
0
2
Order By: Relevance
“…These studies also showed dose-sparing with SCS injection compared with eye drops. Micro-stents penetrated through the scleral spur to generate a fluid conduit from the anterior chamber into the SCS have been shown to reduce IOP in glaucoma patients[48, 57, 91]. …”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…These studies also showed dose-sparing with SCS injection compared with eye drops. Micro-stents penetrated through the scleral spur to generate a fluid conduit from the anterior chamber into the SCS have been shown to reduce IOP in glaucoma patients[48, 57, 91]. …”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Glaucoma is a major eye disorder causing irreversible blindness treated by important device inventions in industrialized countries [1][2][3]. In this research, basic concepts of adaptive implant for minimally invasive glaucoma treatment [4] were studied as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Our initial experiments using these biodegradable polymers as GDD provided promising results [35]. An LDD coating in the outflow area was designed to prevent fibrosis in the postoperative period.…”
Section: Introductionmentioning
confidence: 99%